T cell independent mechanisms for protection against Mycobacterium tuberculosis infection - Bickett, Thomas, author; Izzo, Angelo, advisor; Dow, Steven, committee member; McLean, Jennifer, committee member; Bowen, Richard, committee member; Argueso, Lucas, committee member (Colorado State University. Libraries, 2019)
The live attenuated Mycobacterium bovis strain Bacille Calmette Guérin (BCG) is a potent innate immune stimulator. Innate Immunity provides the host with the ability to immediately respond to invasion by pathogens and can be utilized through the use of molecular adjuvants to trigger specific innate mechanisms leading to adaptive immunity. In the C57BL/6 mouse model of tuberculosis, BCG stimulated immunity causes a significant reduction of M. tuberculosis burden after pulmonary infection. Our studies indicate that BCG induced protection against pulmonary M. tuberculosis through early monocyte recruitment is present as early as 7 days after vaccination. This protection showed longevity, as it did not wane when mice were infected 30 days post vaccination. As BCG induced mycobacterial killing after 7 days, we sought to identify the contribution of different innate immune components to better understand mechanisms required for mycobacterial killing. When BCG was administered through subcutaneous inoculation, we found that there was significant monocyte recruitment in the lungs within 7 days after vaccination. Further studies revealed that killing of mycobacterium is dependent on BCG being viable and is monocyte derived, independent of trained innate immunity, highlighting a novel mechanism for killing M. tuberculosis. With the rise of drug resistant strains of Mycobacterium tuberculosis, new vaccine development is paramount. A better understanding of the BCG vaccine will hopefully lead to the development of a more effective alternative.
Keywords: innate immunity; trained innate immunity; tuberculosis; macrophage; BCG